The Identification of Plants from the Zingiberaceae and Euphorbiaceae Families in a Mini Herbal Garden Based on Halal in Sumberbrantas Village, Bumiaji District, Batu, East Java - Ainur Rosyid Ridho, Muhammad; Purwani, Kristanti Indah (Halal Research, 2025)
Indonesia is recognized for its rich biodiversity, particularly in herbal plants, with the Zingiberaceae and Euphorbiaceae families being prominent in traditional medicine. This study focuses on the identification and documentation of herbal plants from these families in Sumberbrantas Village, Bumiaji District, Batu, East Java, where the favorable climate and fertile soil support their growth. Despite the potential, there is limited documentation of these plants, which is crucial for optimizing their benefits and ensuring adherence to halal cultivation practices. The halal concept encompasses not only the end products but also environmentally friendly cultivation processes compliant with Islamic law, including seed selection, organic fertilization, and post-harvest processing. This research identifies key species such as ginger (Zingiber officinale), turmeric (Curcuma longa), and cassava (Manihot esculenta), highlighting their health benefits and economic potential. The study employs morphological observations and comparisons with botanical literature to ensure accurate identification. The findings reveal that all identified plants are cultivated according to halal principles, enhancing their marketability and sustainability. The results underscore the importance of halal-based mini herbal gardens as a model for integrated herbal plant management, promoting health, economic growth, and environmental sustainability within the local community. This research contributes to the understanding of herbal biodiversity in Indonesia and supports the development of sustainable agricultural practices aligned with halal standards.